Association of posterior cruciate ligament injury in different types of femur racture in Hospital Alor Setar Kedah, a cross sectional study - Singh, Inderjeet Singh A/L Ahtar (2016)
Posterior Cruciate injury in association with ipsilateral femur fracture has been historically underdiagnosed as many cases are missed during the initial trauma. The incidence or proportion of this injury has wide variation and the incidence in our setting is not known. Understanding the proportion and association of posterior cruciate injury with femur fracture enables us to detect the injury early and treat the injury accordingly. The aim of treatment to provide a stable and pain free knee while minimalizing the risk of OA. This aim can achieved if the injury is picked up early so than an early physiotherapy regime can be started. There were total 144 patients included in this study. From this total number 45 patients sustained proximal femur fracture, 62 patient sustained mid shaft fracture femur and 37 of them sustained distal femur fracture. From this 144 patient, 13 patients had PCL injury (9%). Based on the study, 6 out of 13 cases of PCL injury with femur fracture were detected late with one case was detected 6 weeks after injury, three cases were detected 8 weeks after injury, one case was detected 9 weeks after injury and 1 case was detected 10 weeks after injury. The remaining 7 cases of PCL injury was detected early. Out of the 7, 5 were avulsion injury which was picked up by x-ray during the initial assessment and the other 2 were picked up following the fixation of femur. The proportion of PCL injury with femur fracture is 9% in our setting and distal 3rd femur fracture have higher incidence. Majority of the cases that were missed was due to failure to perform complete knee examination following fixation. We strongly recommend all patient undergoing femur fracture fixation should undergo complete knee examination while still under anaesthesia. These patient, especially with distal 3rd femur fracture should also be repeatedly screen during clinic their follow up.